Taṭwīr al-Wasīlah al-Ta‘Līmiyyah "Biṭāqah Ūnū" Lli-Tarqiyah Isti'āb al-Mufradāt - Ainunjariyah, Tastabina Putri; Anam, Syamsul; Huda, Mokhammad Miftakhul; Nisa', Dwi Khoirotun (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
The purpose of this study was to understand the process of developing Uno Card learning resources to improve Arabic vocabulary comprehension and to determine their effectiveness for seventh-grade female students at the Darul Istiqomah Islamic Boarding School in Bondowoso during the 2024/2025 academic year. This study employed a research-and-development methodology based on the ADDIE model. Data were collected through observation, interviews, questionnaires, pre-tests, and post-tests. For data analysis, the researcher used an independent sample t-test, and to assess the effectiveness of the product, an N-Gain test was used. The findings of this study are: 1) The development of Uno Cards learning resources was carried out in five stages: analysis, design, development, implementation, and evaluation. The learning material achieved an overall validity score of 95.2% with a "highly valid" criterion, while the learning resources themselves achieved an overall validity score of 100% with a "highly valid" criterion. 85% of students gave this learning tool a very good rating. The calculated t-value of 7.502 was greater than the tabulated t-value of 2.002, indicating rejection of H0 and acceptance of Ha. This showed that the Uno card learning tool was effective in improving seventh-grade students' Arabic vocabulary comprehension. The average N-Gain score in the experimental class was 60.08, which falls into the "fairly effective" category according to the effectiveness criteria.